Study of reading habits 1986 - Vara - Weibull, Lennart (University of Gothenburg, 1992)
This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in Västergötland: Essunga, Götene and Vara. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. The respondents had to indicate the importance of a number of qualities for the choice of local morning paper, and also the importance of receiving news from certain geographical areas. Other questions dealt with how much of the stuff published about sport, economy, political news etc. the respondent was interested in to read. A comparison was done between the news report in local papers, evening papers, television, national radio and local radio.

This survey forms part of the research program ´Dagspresskollegiet´. The target group of this survey was the inhabitants of three municipalities in Västergötland: Essunga, Götene and Vara. Most of the questions are replications of questions asked in previous readership studies, i.e. questions concerning reading habits, subscriptions of papers, reading interests and background variables such as gender, age, education and party preference. There were also a number of questions not asked in previous surveys. The respondents had to indicate the importance of a number of qualities for the choice of local morning paper, and also the importance of receiving news from certain geographical areas. Other questions dealt with how much of the stuff published about sport, economy, political news etc. the respondent was interested in to read. A comparison was done between the news report in local papers, evening papers, television, national radio and local radio.
Läsvanestudien 1986 - Vara
Keywords: internal politics; inrikespolitik; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap